Patterns in the influence of funding and reimbursement on the development and implementation of healthcare innovation: A systematic review - Sanne Allers; Frank Eijkenaar; Erik M. van Raaij; Frederik T. Schut (Journal of Open Innovation: Technology, Market and Complexity)
Innovation is considered essential to the quality and sustainability of healthcare systems. However, the path from innovative idea to adopted reality is complex and fraught with barriers. The way in which healthcare innovations are financed is often mentioned as a major stumbling block, but a comprehensive overview of the role payment mechanisms play in innovation processes is lacking. To fill this knowledge gap, we conducted an extensive literature review, combining a systematic data search with textual narrative synthesis. We contextualize the literature on the role of funding and reimbursement in the process of healthcare innovation in relation to stage-gate models of innovation processes. This results in a ‘financial fugle model’ in which the role of funding and reimbursement is analyzed in three consecutive phases of the innovation process: development, translation, and implementation. From the review of 157 included articles, four key findings stand out: 1) shortcomings in national reimbursement systems result in local fragmentation in the implementation of innovations; 2) lack of evidence on costs and benefits in financial decision-making may harm the development and implementation of potentially value-enhancing innovations; 3) more disruptive innovations encounter larger financial barriers; and 4) non-financial factors, including innovator characteristics and institutional support, are essential in overcoming financial barriers. Based on these key findings, we develop a research agenda for further investigation of the influence of payment mechanisms on the process of healthcare innovation.